A histopathological study of gastric mucosal biopsies in infantile hypertrophic pyloric stenosis. Issue 6 (June 1979) - Batcup, G; Spitz, L
Abstract : Gastric biopsies from 35 infants with hypertrophic pyloric stenosis have been assessed for histological features of gastritis. No erosions were found, and there was no excess cellular infiltration of the lamina propria compared with a control group. Fresh haemorrhage into the lamina propria was frequent in both pyloric stenosis and control sections.